2012
DOI: 10.3324/haematol.2011.047613
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome by early bone marrow response in childhood acute lymphoblastic leukemia treated in the ALL-BFM 95 trial: differential effects in precursor B-cell and T-cell leukemia

Abstract: BackgroundIn the ALL-BFM 95 trial for treatment of acute lymphoblastic leukemia, response to a prednisone pre-phase (prednisone response) was used for risk stratification in combination with age and white blood cell count at diagnosis, response to induction therapy and specific genetic high-risk features. Design and MethodsCytomorphological marrow response was prospectively assessed on Day 15 during induction, and its prognostic value was analyzed in 1,431 patients treated on ALL-BFM 95. ResultsThe 8-year prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 40 publications
4
58
0
1
Order By: Relevance
“…This study confirms that T-cell ALL remains a more aggressive disease than B-cell ALL and that additional treatment options need to be explored for T-ALL. 1,4 Recent studies have identified new targets for therapy in T-ALL, 5 although trials to investigate the importance of new targeted drugs will be difficult due to the relatively low number of T-ALL patients (about 10% of ALL cases). 1 Similarly, patients in the NCI (National Cancer Institute) high-risk group had only 82.9% 5-year overall survival, while patients from the standard risk group had 95% 5-year overall survival.…”
mentioning
confidence: 99%
“…This study confirms that T-cell ALL remains a more aggressive disease than B-cell ALL and that additional treatment options need to be explored for T-ALL. 1,4 Recent studies have identified new targets for therapy in T-ALL, 5 although trials to investigate the importance of new targeted drugs will be difficult due to the relatively low number of T-ALL patients (about 10% of ALL cases). 1 Similarly, patients in the NCI (National Cancer Institute) high-risk group had only 82.9% 5-year overall survival, while patients from the standard risk group had 95% 5-year overall survival.…”
mentioning
confidence: 99%
“…Response of leukemic tumor burden to glucocorticoids is said to be the strongest predictor of outcome of the treatment of ALL. 7,8 Most of the studies were carried out using prednisolone. Therefore, this study was designed to see the effect of dexamethasone on tumor load and their relationship with response to induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,[31][32][33] The general message for the individual patient is simple: the fast reduction or even elimination of the leukemia (or its predominant clone) is highly predictive of superior relapse-free survival. 8,34 Borowitz et al clearly demonstrated that distinct levels of MRD (by FCM) in the peripheral blood at day 8 of induction therapy in a large set of precursor B-cell (pcB) ALL patients (n ϭ 2143) were associated with the probability of EFS (pEFS).…”
Section: Mrd Levels At Predefined Time Points May Predict Success Of mentioning
confidence: 99%
“…3 Despite the clear separation of risk groups by BM cytology, 2/3 of the relapses occur in patients with M1 or M2 BM on day 15 of induction. 4 Therefore, advanced and highly sensitive methods for response assessment were needed and developed to detect minimal residual disease (MRD). The choice of technique for MRD detection mainly depends on the aims of the clinical trial and on the availability of resources.…”
Section: Introductionmentioning
confidence: 99%